Implementasi Budaya Religius dalam Pembentukan Akhlak Siswa di MTsN 16 Jombang - Muhammad, Ravi Yusuf; Ashoumi, Hilyah (Universitas KH. A. Wahab Hasbullah, 2023)
The purpose of this study was to determine the strategy of implementing a religious culture in shaping student morals at MTsN 16 Jombang. This research is descriptive using a qualitative approach, the researcher is the key instrument, data collection techniques are triangulated (combined), data analysis is inductive and research results emphasize meaning rather than generalization. The strategy of implementing a religious culture in the formation of student morals at MTsN 16 Jombang is pursued through a personal approach where this approach is mostly done to overcome problematic students, make mistakes or violations of school rules and habituation of daily activities with religious nuances, these activities are carried out simultaneously so that they become a madrasa culture, among others; habituation of greetings that foster an attitude of tolerance and respect for elders, praying together before starting lessons that foster an attitude of discipline and responsibility, reading the Qur'an (Tadarus al-Qur'an) in its implementation fosters an attitude of awareness of the obligation to worship properly and correctly and dhuhur prayers in congregation, this activity fosters an attitude of solidarity and togetherness.